ANALISIS KEPERCAYAAN, KEMUDAHAN PENGGUNAAN, PENGALAMAN BERBELANJA TERHADAP KEPUTUSAN PEMBELIAN DI SITUS JUAL BELI ONLINE LAZADA DI KARAWANG - Putta, Ariyananda Pantana; Saluy, Ahmad Badawi (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2019)
ABSTRACT This study aims to analyze Trust, Ease of Use, Shopping Experience of Purchasing Decisions on the Lazada Online Buying and Selling Site in Karawang. In this study, the population was internet users in Karawang who had shopped online at least once at Lazada.com and other sites. This study uses a Non Probability Sampling technique by Purposive Sampling. The results of this study indicate that (1) Trust has a positive and significant effect on Purchasing Decisions on Lazada Online Buy and Sell Sites, Ease of Use has a positive and significant effect on Purchasing Decisions on Buying and Selling Sites Lazada Online, (3) Shopping Experience has a positive and significant effect on Purchasing Decisions on the Lazada Online Buying and Selling Site, and (4) Trust, Ease of Use and Experience of Shopping together have a positive and significant effect on Purchasing Decisions. It is recommended that Lazada maintain consumer confidence through increasing popularity and e-commerce imagery in order to increase the existence of Lazada among the public by participating in various events